1999
DOI: 10.1002/(sici)1096-8652(199903)60:3<191::aid-ajh4>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bcl-2 by human bone marrow mast cells and its overexpression in mast cell leukemia

Abstract: Bcl-2 protein plays a major role in the prevention of programmed cell death of differentiating cells. In the present study, the expression of cytoplasmic bcl-2 by human Bone Marrow Mast Cells (BMMC) from both normal and pathological bone marrow samples was examined. A total of 35 subjects corresponding to 9 healthy volunteers, 8 cases of adult indolent systemic mast cell disease (SMCD), 4 cases of pediatric mastocytosis (PM), 11 cases of hematological malignancies (HM), 2 cases of reactive bone marrow, and 1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…11,22 Two previous studies have addressed the role of bcl-2 proteins in mastocytosis. 34,35 Using immunohistochemistry, Jordan et al 34 have demonstrated that mast cells in focal bone marrow infiltrates of adult patients with systemic mastocytosis show strong immunoreactivity for bcl-xL, but usually fail to express bcl-2. Out of 22 patients investigated, only one patient with mast cell leukemia was found to express bcl-2 in a small fraction of bone marrow mast cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11,22 Two previous studies have addressed the role of bcl-2 proteins in mastocytosis. 34,35 Using immunohistochemistry, Jordan et al 34 have demonstrated that mast cells in focal bone marrow infiltrates of adult patients with systemic mastocytosis show strong immunoreactivity for bcl-xL, but usually fail to express bcl-2. Out of 22 patients investigated, only one patient with mast cell leukemia was found to express bcl-2 in a small fraction of bone marrow mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 22 patients investigated, only one patient with mast cell leukemia was found to express bcl-2 in a small fraction of bone marrow mast cells. In accordance, Cervero et al 35 have reported on one patient with mast cell leukemia and overexpression of bcl-2, as assessed by quantitative flow cytometry, in bone marrow mast cells as well as peripheral blood mast cells that were present in this case. Eight other patients with indolent systemic mastocytosis expressed normal levels of bcl-2 in bone marrow mast cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 Knowledge about the role of Bcl-2 family members in the regulation of mast cell survival and apoptosis is limited. It has been shown that Bcl-2 and Bcl-X L are expressed in mast cells, [11][12][13] but very little is known about their function in these cells. It has been reported that baxÀ/À and bcl-2À/À mice have abnormal numbers of mast cells in certain tissues but no general difference with wt animals were observed.…”
Section: Introductionmentioning
confidence: 99%